O regime constitucional da região metropolitana - Serrano, Pedro Estevam Alves Pinto (2009)
The present monograph aims to formulate the description of the metropolitan region in the Brazilian constitutional system. Among the situations concerning the theme, the present work is focused on both district and state s role when creating the metropolitan region as well as what will happen to the competency, organization and administration of the area by the district and by the state, specially opposed to the fact that we are dealing with a urban sprawl. The importance of finding out the metropolitan region s legal system urges from the reflex effects of these analysis, implying the formulation of a legal definition of this institute and it is from this definition that we intend to solve the questions related to the federal union being entitled to do public services, to do activities using public proprieties, such as the production of treated water, the service of water and sewage distribution, the garbage collection and its final destination or the intermunicipal public transportation. We also intend to go through questions concerning the legislative scope, such as the competency to legislate about the ground s use and occupation, the preservation of the urban environment and the regulation of the fountainhead areas, the re-urbanization of degraded areas, industrial activities and so on. To achieve the aim of defining the metropolitan region s legal system we had to formulate the prerequisites from the auxiliary elements to the dogmatic interpretation, for instance the conformation of the State and the political power, the federative system, historical incursions about the federation and its confrontation to the comparative law, the role of the district and the state and finally get into the analyses of the metropolitan region, arguing about its creation, its competency, its administration, its relation with the conception of consortiums and conventions and, for example, who is entitle of providing basic sanitation services